Calling, life satisfaction and job satisfaction: religion as a moderator - Jaramillo, Matthew, author; Chavez, Ernest L., advisor; Dik, Bryan J. (Bryan Jay), advisor; Anderson, Sharon K., committee member (Colorado State University. Libraries, 2011)
Research has suggested that people who approach their work as a calling are more likely to report higher life satisfaction and job satisfaction than those who do not. Different Christian denominations may have different approaches to how they view work, however. Research has also supported the idea that people who are intrinsically religious are more likely to interpret their work in a religious way. People who are extrinsically religiousness may not interpret their work in the same way. This study examined calling's relation to life satisfaction and job satisfaction, using denomination, intrinsic religiousness, and extrinsic religiousness as moderators. Participants were 215 employees at a large western university who identified themselves as Christians. They were classified into one of three categories: Non-Evangelical Protestant (n = 107), Evangelical Protestant (n = 60), and Catholic (n = 48). Hierarchical regression analyses were run which treated religious denomination, intrinsic religiousness, and extrinsic religiousness as moderators. Calling and religious denomination significantly predicted job satisfaction and life satisfaction, but the interaction between the predictors did not significantly predict the satisfaction variables beyond what had been predicted by the main effects alone. The interaction between calling and intrinsic religiousness, however, significantly predicted life satisfaction and job satisfaction. The interaction between search for calling and extrinsic religiousness did not significantly predict life satisfaction or job satisfaction beyond what had been predicted by the main effects alone. Results suggest that intrinsic religiousness moderates the relationship between calling and life satisfaction and job satisfaction and that denominational differences and extrinsic religiousness may not. Implications for research and practice are considered.